2020
DOI: 10.1155/2020/2746492
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Microbial Contamination of Street-Vended Chicken Products Sold in Nairobi County, Kenya

Abstract: Food safety problems pose a great threat to the health of consumers with the greatest burden in developing countries. Street-vended foods play a key role in providing many urban dwellers with cheap, nutritious, and accessible food, but when prepared in an unhygienic and unregulated environment, they could contribute to increased food safety burden. The study investigated the microbiological recovery of work surfaces and chicken sold in Korogocho and Kariobangi North slums in Nairobi County as well as evaluatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 33 publications
5
50
1
Order By: Relevance
“…Food safety problem is the important problem that is a threat to the health of the population [ 1 , 2 ], especially in the developing countries. The major trouble of food safety is food poisoning by the contamination of microorganisms such as bacteria and fungi.…”
Section: Introductionmentioning
confidence: 99%
“…Food safety problem is the important problem that is a threat to the health of the population [ 1 , 2 ], especially in the developing countries. The major trouble of food safety is food poisoning by the contamination of microorganisms such as bacteria and fungi.…”
Section: Introductionmentioning
confidence: 99%
“…These conditions allow dust, flies and exhaust fumes to find their way into the food causing contamination hence posing a health hazard to consumers of these foods. A study by [26] found that only 29% of the vending sites had a canopy while [17] reported that 33% of the vendors in her study were sheltered. Both these findings are contrary to the findings of the present study.…”
Section: B Location Of the Food Vendorsmentioning
confidence: 97%
“…In this study most of the vendors did not wear any protective clothing such as an apron, gloves or covered hair. Similarly, [17] found that out of the 15 street vendors studied, only 8 (53%) wore protective clothing. [16] reported that out of 242 food handlers studied, 21% worked without protective garments, 31.5% wore dirty uniform and 76.6% had no head gear.…”
Section: Food Handling Practices Of the Food Vendorsmentioning
confidence: 98%
See 2 more Smart Citations